Evaluation of Educational programs provided to students with Disabilities in Wadi Al- Dawasir Province in light of the international standards of special education - Merghany, Samar Youssef Ahmed; Ibrahim, Hanadi Issa Muhanna (Journal of Educational and Psychological Sciences, 2020)
The study aimed to evaluate the educational programs provided for students with disabilities in Wadi Al- Dawasir Province in the light of the international standards for special education. Descriptive analytical approach was used, The study sample consisted of (10) programs of special education. A questionnaire of evaluating the educational programs ,was used, "SPSS" was used to analyze the data; the results revealed: an average level of effectiveness for the programs provided for people with disabilities, which ranged between (2.0923) and (2.6154), and there were differences at the level of statistical significance (0.05) between the dimensions of special education indicators, there are statistically significant differences at the level (0.05) due to the following (type of disability, employer, educational qualification, years of experience, degree), The researchers recommend training teachers on educational programs in accordance with international standards.
Keywords: Educational programs; Students with disabilities; International standards of Special education